Dampak Interaksi Investasi Asing Langsung Dengan Stabilitas Perekonomian Terhadap Ketimpangan Pendapatan di Negara Berkembang - Dwi Nadila Bratha; Doni Satria (Universitas Negeri Padang, 2025)
This study aims to analyze the impact of foreign direct investment interactions with economic stability on income inequality in developing countries from 2013 to 2022. This study uses a moderation analysis model (MRA) with a fixed effect model approach in Eviews 12. The results of this study indicate that foreign direct investment has a negative and significant relationship with income inequality; the interaction between foreign investment and economic stability has a positive and significant relationship with income inequality; governance, as indicated by political stability and digitalization variable, has a negative and significant relationship with inequality; governance, as indicated by control of corruption, voice and accountability, and economic growth variable, has no effect on income inequality.